A comparative study between intraoral external oblique ridge fixation with transbuccal lateral cortical plate fixation for treatment of mandibular angle fractures, a prospective study. Issue 2 (2nd April 2018) - Chari, Haripriya; Rao, Brahmaji; Kumar, Pavan; Shaik, Khadar Vali
No abstract available